Characterization and emulsifying properties of different sunflower phosphatidylcholine enriched fractions - Guiotto, Estefania Nancy (2013)
Fractions enriched in specific phospholipids are desirable for different industrial purposes because of their characteristic physicochemical and functional properties. We studied the fractionation process of sunflower lecithin using different absolute-ethanol:water ratios and pHs and then evaluated the emulsifying properties of phosphatidyl-choline- (PC-) enriched fractions in oil:water 30:70 (v/v) mixtures. We observed a high recovery of PC and a low content of phosphatidyl inositol in all the PC-enriched fractions thus obtained along with the highest yields of this phospholipid after extraction with an absolute-ethanol:water mixture of 96:4 (v/v). The use of different pH values for the different solvent extraction media did not markedly modify the yield of the enriched fractions. The extraction coefficients for PC and phosphatidyl ethanolamine (PE) evidenced an increase in both these phospholipids in the PC-enriched fractions upon extraction with the higher concentration of absolute ethanol. Emulsions containing the PC-enriched fractions obtained with the absolute-ethanol:water mixture of 96:4 (v/v) exhibited the highest stability at pH 7.5 because of the high PC/PE ratio compared to that of the PC-enriched fractions extracted with the absolute-ethanol:water mixture of 90:10 (v/v). A high emulsifier concentration resulted in a low mean D-[4,3] diameter of the particles and a high stability.